Treatment Strategies for Distal Clavicle Fractures: A Narrative Review - Yue L; Huang C; Zhang J; Wang Z; Wang S; Sun H (Orthopedic Research and Reviews, 2025)
Lei Yue,* Changsheng Huang,* Jianming Zhang, Ziqi Wang, Shijun Wang, Haolin Sun Department of Orthopedics, Peking University First Hospital, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Haolin Sun, Department of Orthopedics, Peking University First Hospital, 8 Xishiku Street, Xicheng District, Beijing, 100034, People’s Republic of China, Email sunhaolin@vip.163.comAbstract: Distal clavicle fractures, accounting for a significant portion of clavicle fractures, present a treatment challenge due to their high non-union rate and the controversy surrounding operative versus non-operative management strategies. This review synthesizes recent studies and clinical evidence to compare the effectiveness of operative and non-operative approaches for distal clavicle fractures. It discusses the anatomical and classification aspects of these fractures, the indications for surgery, and the rationale behind different treatment options. Surgical fixation, predominantly through locking plates or hook plates, generally provides high union rates and stable outcomes; however, complications such as hardware irritation, subacromial impingement, and implant removal rates are significant concerns. Recent surgical advancements, including ligament repair, distal augmentation, and arthroscopic techniques, have shown promise in improving outcomes. Conversely, conservative treatment is recommended for certain fracture types, with emerging evidence suggesting it provides comparable functional outcomes to those of surgical methods. Despite a high non-union rate, non-operative treatment can be effective in restoring functions. However, challenges such as symptomatic nonunion and osteoarthritis are noted. The choice between surgical and conservative treatments depends on multiple factors, including fracture type, patient age, activity level, and overall health status. This review highlights the need for a personalized approach in managing distal clavicle fractures, considering the evolving evidence and advancements in treatment strategies.Keywords: distal clavicle fracture, surgery, conservative treatment, neer classification